Shakespearean gothic - Desmet, Christy, 1954-2018; Williams, Anne (Gothic literary studies., 2009)
This book explores the paradox that the Gothic (today's werewolves, vampires, and horror movies) owe their origins (and their legitimacy) to eighteenth-century interpretations of Shakespeare. As Shakespeare was being established as the supreme British writer throughout the century, he was cited as justification for early Gothic writers' fascination with the supernatural, their abandoning of literary "decorum," and their fascination with otherness and extremes of every kind.